Proteolysis of ovine and caprine Caseins in solution by enzymatic extracts from flowers of Cynara cardunculuso - Sousa, M. José (2011)
Primary proteolysis of ovine and caprine Na-caseinate at 30°C in phosphate buffer at pH 6.5 or 5.5 in the absence of NaCl and at pH 5.2 with 5% (w/v) NaCl by cardosins in aqueous extracts of Cynara cardunculus flowers was investigated using urea-polyacrylamide gel electrophoresis and reversed-phase high performance liquid chromatography. Caprine caseinate underwent more extensive degradation than ovine caseinate under the same conditions (pH 6.5 and pH 5.5); proteolysis of b- and as-caseins in ovine and, to a lesser extent, in caprine caseinates was reduced in the presence of 5% (w/v) NaCl. Peptide profiles of the pH 4.6-soluble extract had different patterns throughout ripening arising from the different specificity of cardosins toward ovine and caprine Na-caseinates. The major cleavage sites in ovine (caprine) caseinate were Phe105-Met106 (Lys116-Thr117) for k-casein, Leu127-Thr128 and Leu190-Tyr191 (Glu100-Thr101, Leu127-Thr128, Leu136-Pro137 and Leu190- Tyr191) for b-casein, Phe23-Val24 (Phe23-Val24, Trp164-Tyr165 and Tyr173-Thr174) for as1-casein and Phe88-Tyr89 (Ser9-Ser10, Phe88-Tyr89 and Tyr179-Leu180) for as2-casein.